Balance of sugarcane plantation land needs in Lamongan Regency in 2031 based on land-use changes using SPOT imagery - Salis Deris Artikanur; Widiatmaka, Widiatmaka; Setiawan, Yudi; Marimin, Marimin (Jurnal Pengelolaan Sumberdaya Alam dan Lingkungan (Journal of Natural Resources and Environmental Management), 2021)
The volume of Indonesia’s sugar imports in 2019 reached 4,09 million tons. The high volume of imports was influenced by the decreasing area of sugarcane plantations. Lamongan Regency is one of the sugarcane and sugar-producing regencies in East Java. Sugarcane and sugar production in Lamongan Regency has experienced quite diverse dynamics and has been influenced by changes in land-use conditions. This study aims to analyze the balance of land needs for sugarcane plantations in Lamongan Regency in 2031 based on an analysis of land-use changes using SPOT imagery of 2007, 2013, and 2019. The study was conducted by analyzing land-use changes, population projections, and land demand balance analysis for sugarcane plantations. The results of the analysis showed that the population of Lamongan Regency in 2031 is projected to reach 1.419.843 people with a land requirement for sugarcane plantations of 2.362,29 ha. There will be a land surplus of 1.276,92 ha but it is still concentrated in 7 of the 27 sub-districts. Sugarcane plantations in Lamongan Regency have the potential to be developed considering that the land allocation for plantations in the Lamongan Regency Spatial Plan of 2011-2031 reaches 10.022,42 ha.